The structural reconformation of peptides in enhancing functional and therapeutic properties: Insights into their solid state crystallizations - Saadi, Sami; Mohd Ghazali, Hasanah; Saari, Nazamid; Abdulkarim, Sabo Mohammed (Elsevier, 2021)
Therapeutic peptides derived proteins with alpha-reconformation states like antibody shape have shown potential effects in combating terrible diseases linked with earlier signs of angiogensis, mutagenesis and transgenesis. Alpha reconformation in material design refers to the folding of the peptide chains and their transitions under reversible chemical bonds of disulfide chemical bridges and further non-covalence lesions. Thus, the rational design of signal peptides into alpha-helix is intended in increasing the defending effects of peptides into cores like adjuvant antibiotic and/or vaccines. Thereby, the signal peptides are able in displaying multiple eradicating regions by changing crystal-depositions and deviation angles. These types of molecular structures could have multiple advantages in tracing disease syndromes and impurities by increasing the host defense against the fates of pathogens and viruses, eventually leading to the loss in signaling by increasing peptide susceptibility levels to folding and unfolding and therefore, formation of transgenic peptide models. Alpha reconformation peptides is aimed in triggering as well as other regulatory functions such as remodulating metabolic chain disorders of lipolysis and glucolysis by increasing the insulin and leptin resistance for best lipid storages and lipoprotein density distributions.